Performance of optical and hybrid joint transform correlators for tasks of optical security - Muravsky, L.I.; Kulynych, Ya.P.; Maksymenko, O.P.; Voronyak, T.I.; Pogan, L.Y.; Vladimirov, F.L.; Kostyukevych, S.A.; Fitio, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Performance of optical and hybrid joint transform correlators (JTCs) for security verification of optical marks containing transformed phase masks (PMs) is studied. The peak-to-noise ratio (PNR) and relative intensity of correlation peaks are selected as basic criteria for comparative analysis of such two types of JTCs. The theoretical model of an interference noise produced as a result of an input and reference binary PMs cross-correlation on a conventional JTC output is developed. The optically addressed spatial light modulator (OASLM) based on the chalcogenide glass photoconductor - nematic liquid crystal structure is considered. The experimental setup of an OASLM JTC is designed on the basis of this SLM. The relations a PNR and relative intensity versus an effective focal length of an optical Fourier processor are studied and the basic reasons limiting efficiency of the setup are analyzed. The optoelectronic device for identification of credit cards based on a hybrid optical-digital JTC architecture is built. The conditions of a joint power spectrum recording by a CCD-camera in this device are investigated. The concluding about expediency of OASLM JTC and optoelectronic device usage for different security applications is made.